2006
DOI: 10.1203/01.pdr.0000233075.48306.57
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of KATP Channels and Endothelin-1 in Lambs With Persistent Pulmonary Hypertension of the Newborn

Abstract: Persistent pulmonary hypertension of the newborn is a life-threatening condition in which half of infants fail to respond to inhaled nitric oxide. Development of new therapeutic pathways is crucial. The adenosine triphosphate (ATP)-sensitive potassium channels (K ATP ) may be important in this condition. Concentrationresponse curves to the K ATP channel opener (SR47063) were performed in isolated pulmonary arterial rings from normal newborn lambs (n ϭ 8) and pulmonary hypertensive lambs (n ϭ 7) induced by intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…These findings suggest that any intervention aiming at reducing IRI that involves IL‐6 or ET‐1 must take place during organ retrieval or even earlier. Further studies designed to more precisely delineate the role of these cytokines in IRI could include already‐available antagonists (26–29). Longer CI times, such as those reported in clinical practice, may increase the benefit of early intervention and interruption of the inflammatory cascade, but this hypothesis needs to be tested in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that any intervention aiming at reducing IRI that involves IL‐6 or ET‐1 must take place during organ retrieval or even earlier. Further studies designed to more precisely delineate the role of these cytokines in IRI could include already‐available antagonists (26–29). Longer CI times, such as those reported in clinical practice, may increase the benefit of early intervention and interruption of the inflammatory cascade, but this hypothesis needs to be tested in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…ET B vasodilatory effects were maintained during the first few days after the onset of PH, but these eventually became suppressed. Around the same time period, ET A ‐mediated vasoconstriction became more pronounced, and this was concomitant with an increase in pulmonary resistance 80 . In PAs of newborn sheep that were born and maintained at high altitude, chronic hypoxia increased the sensitivity of contraction to ET‐1 7 .…”
Section: Mechanisms Of Pulmonary Vasoconstrictionmentioning
confidence: 97%
“…Around the same time period, ET A -mediated vasoconstriction became more pronounced, and this was concomitant with an increase in pulmonary resistance. 80 In PAs of newborn sheep that were born and maintained at high altitude, chronic hypoxia increased the sensitivity of contraction to ET-1. 7 Yet such programming may occur after birth because ET-1 constriction was maintained in PAs from fetal sheep exposed to maternal chronic hypoxia.…”
Section: Hypoxia-induced Pulmonary Vasoconstriction (Hpv)mentioning
confidence: 99%
“…Extensively oxidized LDL (oxLDL) is exceedingly atherogenic (Chen et al, 2010). Recently, ATP-sensitive potassium channel openers have been shown to enhance NO release, reduce levels of mRNA for endothelin-1, exert antiapoptotic effects, and inhibit the overexpression of adhesion molecules in aortic endothelial cells under metabolic disturbances induced by oxidized low-density lipoprotein (Maurey et al, 2006). Furthermore, it has been demonstrated that the opening of K ATP channels attenuates vascular and cardiac remodeling due to chronic inhibition of NO synthesis and induction of endothelin-1 synthesis (Gao et al, 2009).…”
Section: Scuss Onmentioning
confidence: 99%